2020
DOI: 10.1155/2020/5162524
|View full text |Cite
|
Sign up to set email alerts
|

From the Performance to the Essence: The Biological Mechanisms of How Tantalum Contributes to Osteogenesis

Abstract: Despite the brilliant bioactive performance of tantalum as an orthopedic biomaterial verified through laboratory researches and clinical practice in the past decades, scarce evidences about the essential mechanisms of how tantalum contributes to osteogenesis were systematically discussed. Up to now, a few studies have uncovered preliminarily the biological mechanism of tantalum in osteogenic differentiation and osteogenesis; it is of great necessity to map out the panorama through which tantalum contributes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Further comprehensive and longer studies need to be conducted to optimize the scaffolds, as the main focus of this study was to introduce the newly developed high interface-strength scaffold and assess its osteointegration activity. As for the specific mechanisms through which Ta scaffolds promote osteointegration, including osteogenic differentiation, osteogenesis, and osteoinduction, various hypotheses have been proposed [ 55 ]. Shi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Further comprehensive and longer studies need to be conducted to optimize the scaffolds, as the main focus of this study was to introduce the newly developed high interface-strength scaffold and assess its osteointegration activity. As for the specific mechanisms through which Ta scaffolds promote osteointegration, including osteogenic differentiation, osteogenesis, and osteoinduction, various hypotheses have been proposed [ 55 ]. Shi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Integrating these results, we concluded that dysregulation of Wnt pathway may mediate the contrition of prognostic AGRs to the prognosis of OS patient. Wnt pathway was a crucial cascade involved in stemness and development, and aberrant Wnt pathway was usually implicated in tumorigenesis and progression [ 55 , 56 ]. It has been proved that there was a dual feedback regulation between Wnt pathway and autophagy [ 57 ], and GSVA analysis revealed that the negative regulation of autophagy was also hindered in the high-risk group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ta has been known as a biocompatible metal with superior properties in terms of corrosion resistance and bioactivity, consequently it has been considered for surgical implants [ 161 ]. The addition of tantalum to bioactive glasses has been reported in different investigations [ 151 , 162 – 172 ].…”
Section: Bioactive Glasses Doped With Other Elementsmentioning
confidence: 99%